Hormonal assay in lactating male goat - KUMAR, DAVENDRA; SAHA, S; CHATURVEDI, O H; KUMAR, S; MANN, J S; MITTAL, J P; SINGH, V K (The Indian Journal of Animal Reproduction, 2023)
This communication reports a case of an extremely rare incidence of lactation in an adult fertile male goat. The serumconcentration ofprolactin, progesterone, testosterone and estradiol hormones of a lactating male, normal male and female goatwere found to be 5.40, 2.40 and 1.90 ng/ml, 144.00, 22.60 and 1.90 nmol/1, 5.00, 18.60 and 0.748 nmol/1 and 62.84, 90.97 and94.80 pmol/1, respectively. The high concentration ofprolactin and progesterone with low concentration of testosterone andestradiol hormones in the lactating male goat as compared to normal male might have been responsible for lactation in the malegoat.
Keywords: lactation; teats; mammary gland; hormones and male goat